Impact of Crisis Coverage on the Financial Market of Russia - E. A. Fedorova; S. O. Musienko; F. Yu. Fedorov; l. V. Vinogradova (Финансы: теория и практика, 2019)
The article examines the impact of informational messages characterizing the crisis in the economy on the financial market indicators. The aim of the article is to build an index that allows assessing the crisis situation in the country based on textual analysis of informational messages. Due to the literature review, the factors determining the crisis in the economy were identified. The empirical base of the study included more than 10 million news texts from various sources accredited by Thomson Reuters. For the first time, the authors compiled a “bag of words” (dictionary) to determine the crisis situation in the country; and by means of the text analysis, they developed the author’s crisis index calculated on the basis of news reports in foreign media about Russia. They conducted the analysis of the relations between the crisis index and the stock index MOEX. According to the results of the study, it has been established that an increase in the number of news reports determining the crisis situation in the economy has a negative effect on the financial market: it leads to a drop in stock prices. Thus, not only objective economic factors, but also the information component influencing the mood of investors and the behavior of economic entities, affects the key indicators of the financial market. The proposed author’s crisis index can also be used to assess other relations, for example, the effect of the crisis on the exchange rate.